Click Chemistry Protocol for 3D Bioprintable Elastin−Hyaluronic Acid Hydrogels. Issue 2 (16th December 2022) - Cadamuro, Francesca; Sampaolesi, Susanna; Bertolini, Giulia; Roz, Luca; Nicotra, Francesco; Russo, Laura
Abstract: The generation of 3D‐bioprintable and biocompatible hydrogels based on elastin and hyaluronic acid is described. The procedure is based on a biocompatible click reaction between maleimide and thiol for the final crosslinking, employable with living cells due to fast kinetics and absence of side products. To this end, both α‐elastin and hyaluronic acid were functionalized with linkers ending with maleimide groups, at controlled functionalization intensities, and crosslinked with a dithiol−PEG linker. Varying the equivalents of the three reagents, four different hydrogels were obtained and their biocompatibility, swelling capacity and printability were tested. Biological experiments were performed with human lung fibroblast, human bronchial epithelial and human endothelial cell lines cultured in the hydrogels. Fibroblasts and epithelial cells can survive and proliferate. Epithelial cells showed an increased expression of CD44 and integrin αv β3. Gene expression analysis revealed up‐regulation of metalloproteinases both in normal fibroblast and epithelial cells. Abstract : α‐Elastin is a natural component of the extracellular matrix, which guarantees elasticity and extensibility to the tissue. Its application in tissue engineering is limited due to the difficulties in controlling its physical properties and handiness in biomaterials formulation. In this study, a method to functionalize elastin was investigated to obtain a 3D printable hydrogel by crosslinking with hyaluronic acid.